Analysis of the Effects of the Number of Blades on the Performance of the Archimedes Turbine - Danial, Danial; Junaidi, Junaidi (Fakultas Teknik dan Ilmu Komputer, 2025)
Hydropower conversion technology into electrical energy has been widely found. Technology for small scale with small hydro capacity, especially for power plants in remote villages, is still a challenge. The right technology for villages must be easy to manufacture, maintain, and use components that are easy to obtain. One technology that suits this condition is the Archimedes turbine generator. In this study, an analysis of the performance of the Archimedes turbine prototype as a hydroelectric power plant with 1 blade and 2 blade was carried out. The results of measurements and analysis showed that the 2-blade turbine provided better rotation, work discharge, and turbine efficiency compared to the 1-blade turbine. The 2-blade turbine provided better performance compared to the 1-blade turbine. The measurement results also found that the turbine performance would be better if installed at an angle of 30O.